(3OjhGf MjU HjUs - (3CHhGdahGQS SYO Hf eMeO Hf SYO GdJejej, MjU HjU,J (B574 (3g` s
(3ChdgG (B:s
(3hbGd cGdCaJNGQ(B: (3NPhG ef PeGej YOI ddYhGbH ajG bQH eG Hjfj hHjf GdeWGdH s
(3BNQgG (B:s
(3bUjOI ef eOGFM CejQ GdeDefjf GdeSJVF HCeQ Gddg BNQ GdehLhO efgG(B: (3hRjQ EPG Pd GdNejS Yf GdYOi caGg Qhi UGFH hcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B212s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B93 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B786s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs